1998
DOI: 10.1128/iai.66.5.1869-1877.1998
|View full text |Cite
|
Sign up to set email alerts
|

Cytopathic Effects of the Major Surface Protein and the Chymotrypsinlike Protease ofTreponema denticola

Abstract: Prominent antigens of Treponema denticola have been suggested to be mediators of the cytopathic effects typically seen in periodontal disease. In the present study of the T. denticola major surface protein (Msp) and the surface-expressed chymotrypsinlike protease complex (CTLP), we characterized the ability of these proteins to adhere to and lyse epithelial cells. Msp and CTLP were closely associated in spirochete outer membranes. Purified Msp, both native and recombinant, and CTLP bound to glutaraldehyde-fixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
104
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(110 citation statements)
references
References 70 publications
5
104
0
Order By: Relevance
“…2) showed intriguing patterns of Msp and CTLP expression in the mutant strains that suggested structural interactions between these proteins. These data are consistent with previous studies demonstrating co-localization of Msp and CTLP in the outer membrane [5]. Antigenic epitopes of Msp were predicted to be in the amino terminal half of the molecule, encoded upstream of the HindIII and PstI sites [15].…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…2) showed intriguing patterns of Msp and CTLP expression in the mutant strains that suggested structural interactions between these proteins. These data are consistent with previous studies demonstrating co-localization of Msp and CTLP in the outer membrane [5]. Antigenic epitopes of Msp were predicted to be in the amino terminal half of the molecule, encoded upstream of the HindIII and PstI sites [15].…”
Section: Resultssupporting
confidence: 91%
“…3B, and data not shown). Earlier studies implied that the high molecular mass native Msp oligomeric complex might be structurally associated with the CTLP complex [5,18]. The lack of oligomeric Msp and hexagonal array in strain CKE suggested that CTLP expression might in£uence the production or assembly of the Msp hexagonal array.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Periodontal tissue cells T. denticola cells and individual virulence factors are cytotoxic to epithelial cells [75,92]; they perturb cytoskeletal dynamics [93][94][95][96][97][98] and cell-cell junctions [99,100]. T. denticola can penetrate epithelium [96,101], whereas T. medium also invades epithelial cells [102].…”
Section: Oral Spirochaetes Impact On Host Cellsmentioning
confidence: 99%